The therapeutic potential of cyanidin-3-O-glucoside relating to female reproductive health - Majerik Behinska, Katarina; Balkova, Ema; Mihal, Michal; Roychoudhury, Shubhadeep; Kolesarova, Adriana (Frontiers in Pharmacology, 2025)
Cyanidin-3-O-glucoside (C3G), a dietary flavonoid found in berries, exhibits strong antioxidant, anti-inflammatory, and anticancer properties. It plays a role in female reproductive health by protecting ovarian cells from oxidative stress while inhibiting tumour growth and inducing apoptosis in ovarian and cervical cancer cells. C3G can modulate estrogen receptors, growth factors, and apoptosis- and angiogenesis-related pathways. Its antioxidant and anti-inflammatory properties may be beneficial in hormone-related reproductive disorders and in oncological conditions of reproductive organs, such as ovarian cancer. Beyond its anticancer effects, C3G may be able to mitigate reproductive disorders such as polycystic ovary syndrome (PCOS), although its low bioavailability and need for improved delivery methods pose challenges. C3G influences gut microbiota and enhances systemic antioxidant activity, too. This evidence-based study summarizes the biological effects of C3G, emphasizing its impact on female reproductive health, proposing its mechanism(s) of action, and potential clinical application. Future pre-clinical and clinical investigations are needed to determine C3G’s effective dosages and assessment as a complementary or alternative therapy in gynecological oncology and reproductive health. Moreover, as many of these observations in the literature are based on large in vitro and enzyme-based studies that may be influenced by pan assay interference–a common challenge with some polyphenolic metabolites, such as C3G, the results must be interpreted with caution, and further in vivo, preclinical, and clinical investigations employing orthogonal and physiologically relevant approaches are warranted.